Effects of Pharmacotherapy Training Course on Improving the Drug Prescription Skills of Medical Students: A Pharmacy-based Intervention - Fatemeh Taheri Asl; Mohammadhossein Taherynejad; Maryam Emadzadeh; Mina Akbari Rad; Mohammad Ali Yaghoubi; Amirreza Rostami; Sepideh Hejazi; Mitra Ahadi; Samaneh Sajjadi; Amirali Moodi Ghalibaf; Ali Moradi; Sahar Ravanshad (Future of Medical Education Journal)
Background: Due to the growing issue of medical errors, ensuring safer, and evidence-based prescribing practices, a training course on rational drug prescription for medical students is mandatory. Currently, the training course on rational drug prescription in Mashhad University of Medical Sciences and other faculties has not been defined for medical interns. The present study investigated the effects of a pharmacy-based rational pharmacotherapy training course on improving medical students’ pharmacotherapy knowledge and skills.Method: In 2023, thirty internal internship students of Mashhad University of Medical Sciences were assigned to the intervention and control groups. A pre-test survey was administered to all participants at the beginning of their internal internship. The intervention group underwent a seven-day course on rational pharmacotherapy at the hospital pharmacy unit. In contrast, the control group had their regular internship training. Post-tests were conducted for both groups at the end of their internal internship period. Ultimately, the pre-test and post-test scores were compared between the two groups.Results: A total of 30 interns with an average age of 24.88 ± 0.97 years were included in the study. There was no significant difference in their basic level of prescription knowledge between the two groups (p=0.314). Following intervention, a substantial improvement was noted in the overall post-test score of the intervention group (P=0.001).Conclusion: A pharmacy-based pharmacotherapy training course can substantially improve medical students’ pharmacotherapy knowledge and skills. The present findings advocate for the integration of such courses into the medical education curricula, aiming to enhance rational drug prescription practices among future physicians.